SISTEM INFORMASI PENJUALAN PRODUK FROZEN FOOD TR UMKM BERBASIS WEB - PUTRA, EGA ALDISON; Karyanto, Nonot Wisnu (Melek IT : Information Technology Journal, 2024)
Sales is the process of selling activities that are directly related to consumers. Frozen Food TR (tiara) is a business operating in the frozen food processing sector. The current system requires consumers to go to the shop directly to place an order. The problems faced so far in sales are still experiencing many obstacles, such as managing sales data manually by recording in books, which takes a long time and the entry and exit of goods is still not recorded properly, causing files to be lost. Then the payment transaction process is still carried out in cash so that sales invoices have not been managed properly and errors occur in making reports. The results of this research are to provide solutions and make it easier to access sales reports, thereby helping to speed up work accurately.